PENGARUH KEGIATAN PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) TERHADAP PENINGKATAN EKONOM ANGGOTA PKK DI DESA TANJUNG AGUNG KECAMATAN LENGKITI KABUPATEN OKU - Yopi Yunsepa; Hema Malini; Juliya Arenda (Journal Economics Technology And Entrepreneur, 2026)
This study aims to examine the influence of Family Welfare Empowerment (PKK) activities on improving the economic condition of PKK members in Tanjung Agung Village, Lengkiti District, Ogan Komering Ulu Regency. The study employed a descriptive method with a quantitative approach using simple linear regression analysis. Data were collected through observation, interviews, documentation, and literature review. The analysis produced the regression equation Y = 6.446 + 0.690X, indicating that PKK activities have a positive effect on the economic improvement of its members. The correlation coefficient of 0.733 indicates a strong relationship between the two variables. The coefficient of determination (R² = 0.537) shows that PKK activities contribute 53.7% to the economic improvement of PKK members, while the remaining 46.3% is explained by other factors outside the research model. The t-test results (t = 7.983 > t = 2.004) indicate that PKK activities have a positive and statistically significant effect on improving the economic condition of PKK members.